Hermeneutika Kontekstual dalam Reformasi Islam: Kajian terhadap Pemikiran Nasr Hamid Abu Zayd - Siregar, Anwar Habibi (Medan Resource Center, 2025)
This study analyzes Nasr Hamid Abu Zayd’s critical approach to reforming the understanding of Islamic religious texts. In response to the challenges posed by modernity and globalization, Abu Zayd emphasizes the importance of rationality in interpreting religious teachings. His ideas emerge as a response to the stagnation of Islamic thought, which tends to be scripturalist and ahistorical. The study aims to examine Abu Zayd’s methodological contributions in offering a new paradigm of Qur’anic interpretation that is contextual and inclusive. This research employs a qualitative approach using historical-critical analysis and critical discourse analysis of Abu Zayd’s key works. Data were obtained through a review of primary and secondary literature discussing his interpretative thought and methodology. The results show that Abu Zayd’s contextual approach encourages a progressive and inclusive interpretation of religious texts. He stresses the importance of understanding texts within the historical, social, and cultural contexts in which they emerged. Thus, the interpretation of texts becomes dynamic and relevant to contemporary realities. The discussion highlights how Abu Zayd’s approach opens space for dialogue between text and context and supports the values of pluralism, tolerance, and individual rights in modern Muslim societies. His findings make a significant contribution to the development of critical Islamic studies and help bridge the gap between tradition and social transformation. This study recommends integrating the contextual approach into Qur’anic studies to promote a more open and humanistic Islamic discourse.